Flow features of thermophoretic MHD viscous fluid flow past a converging channel with heat source and chemical reaction - Kalita, B.K.; Choudhury, R. (Zielona Góra: Uniwersytet Zielonogórski)
A boundary layer flow of an electrically conducting viscous fluid past a converging channel in the presence of thermophoresis, heat source, chemical reaction, viscous dissipation and simultaneous heat and mass transfer characteristics is studied in the paper. An external magnetic field of uniform strength is applied transversely to the channel.
Keywords: MHD; viscous fluid; heat source; thermophoresis; Nusselt number; skin friction